Freedom, security and justice area and the European Arrest Warrant: When (no) mutual trust on the conditions of detention justifies their non-implementation - Alves, Dora Resende (2017)
Once the executing judicial authority of an European Arrest Warrant (EAW) can not rely on one of the grounds for non-execution exhaustively listed, it is obliged to surrender the requested person to the judicial authorities of issue even where the provisions of its national law, even if constitutional, confer a higher level of protection of fundamental rights than that arising from the provisions of the Framework Decision. The problem is allowing a Member State to invoke the highest standard of protection of fundamental rights to subordinate the delivery of a convicted person in default could jeopardize the principles of mutual recognition and mutual trust on which the EAW is based and, consequently, its effectiveness. As the importance of the protection of fundamental rights, it is necessary to be aware that the last case-law makes it possible to introduce a systematic exception to the execution of European arrest warrants issued by States which do not comply with the minimum requirements laid down by international law, which would lead to a standstill of the mechanism, and could jeopardize one of the objectives of the area of freedom, security and justice.